Feasibility of rapid quantitation of stratum corneum lipid content by Fourier transform infrared spectrometry. Issue 3 (2004) - Tsai Tsai, Jui-Chen Jui-Chen; Lo Lo, Yu-Li Yu-Li; Lin Lin, Ching-Yu Ching-Yu; Sheu Sheu, Hamm-Ming Hamm-Ming; Lin Lin, Jui-Che Jui-Che
Abstract : The permeability barrier of skin resides in the stratum corneum, and its properties are mediated by a series of lipid multilayers, enriched in ceramides, cholesterol, and free fatty acids, segregated within the stratum corneum (SC) interstices. SC lipid content is usually determined by gravimetric methods in conjunction with high performance thin layer chromatography, but these methods are time‒consuming and involve hazardous solvents. The objective of the present study was to develop a method of measuring SC lipid content by Fourier transform infrared spectrometry (FTIR) that is fast and requires no solvents. The IR spectra of isolated porcine SC sheets were recorded using a FTIR spectrometer. SC lipid content was determined by gravimetric methods using chloroform–methanol extraction. The peak area of both the CH2 symmetric (2850 cm −1 ) and asymmetric (2920 cm −1 ) stretching bands in the IR spectra of progressively solvent‒extracted porcine SC sheets decreased with increasing amount of SC lipids removed. When spectral analysis was performed by curve‒fitting using GRAMS/32 software between 3000 to 2800 cm −1, peak area ratios of CH2 to CH3 asymmetric stretching bands in the IR spectra of 46 isolated porcine SC samples were correlated to SC lipid content ( R 2 =0.90), with the standard error of measurement of 1.91%. The study demonstrated the feasibility of using FTIR technique to rapidly and accurately measure SC lipid content.